Design of fast dissolving amlodipine besylate tablet formulations - Roy, Harekrishna; Parida, Kirti R; Nandi, Sisir; Panda, Sanjay K; Mohapatra, Debendra K (Asian Journal of Pharmaceutics (AJP), 2014)
The demand for fast disintegrating tablets has been growing during the last decade especially for geriatric and pediatric patients because of swallowing difficulties. Amlodipine besylate is used commonly for the treatment angina pectoris, commonly known as angina, which is chest pain due to ischemia of the heart muscle, generally due to obstruction or spasm of the coronary arteries. Hence, in the present work an attempt has been made to formulate fast dissolving tablets of amlodipine besylate by direct compression technique using various concentration of super disintegrants like cross carmellose sodium (Ac-Di-Sol), polyplasdone R-XL and sodium starch glycolate (SSG). The formulated tablets were evaluated for crushing strength, friability, thickness, diameter, weight variation, drug content, wetting time, water absorption ratio, disintegration time, and percentage of drug release. All formulations showed satisfactory result. Among them formulation F3 containing 3% of Ac-Di-Sol exhibited complete release within 12 minutes and disintegration time was within 10 seconds. Dissolution data was compared with innovator for similarity factor (f2) exhibited an acceptable value >50 (82). Accelerated stability study indicated no significant difference in assay and crushing strength. Hence, three production validation scale batches were designed based on lab scale best batch (F3) and charged for stability. All parameters were within the limit of acceptance. There was no chemical interaction between the drug and excipients during FT-IR study; considered in the present investigation.